Surgical treatment of disorders of the menstrual cycle. - Bravo Reyes, Carlos (2015)
Regarding the surgical treatment of disorders of the menstrual cycle, we can say that these can be conditioned mainly to the existence of vaginal bleeding or certain types of disturbance dependent cycle of lack of ovulation, as in polycystic ovary disease.